Russian Economic Report, April 2015 : The Dawn of a New Economic Era? - World Bank Group (Washington, DC, 2015)
Russia's economy experienced two shocks in 2014. On top of the structural crisis that began in 2012, Russia had to deal with cyclical and idiosyncratic challenges to the economy. One of the new shocks illustrates Russia s integration into the world economy through its natural resource exports, and thus its dependence on the global commodity cycle: oil prices more than halved between July and December 2014, giving Russia a terms-of-trade shock. The ruble lost 46 percent of its value against the US dollar, which worsened already eroded business and consumer confidence. The monetary tightening in response made credit expensive, further dampening domestic demand. The other, more idiosyncratic, shock was related to the geopolitical tensions that began in March 2014 and led to economic sanctions. The tensions not only heightened perceptions that Russian investments had become riskier, they also dramatically increased the costs of external borrowing for Russian banks and firms. Spreads on Russian credit default swaps peaked in December at 578 basis points, compared to 159 a year ago. Together with the financial sanctions imposed on Russia in late July, which have restricted the access of Russia s largest state-connected banks and firms to Western international finance markets, this all but extinguished investment. The current World Bank baseline outlook, however, sees the national poverty rate increasing from 10.8 percent in 2013 to 14.2 percent in 2015 and 2016. Poverty is expected to increase because real disposable income and consumption will decline. This would be the first significant increase in poverty rates since the 1998-1999 crises. Russia weathered the 2008- 2009 crisis well as disposable incomes continued to grow slightly. Given the current limited fiscal space, additional support for the poor and vulnerable is likely to be less generous than it was during the 2008-2009 crisis. Although people at the bottom of the income distribution are the most vulnerable, there will be less opportunity for an increase in shared prosperity in 2015-2016, and there is a worrisome possibility that recent achievements might be reversed.